2020
DOI: 10.1021/jacs.0c10339
|View full text |Cite
|
Sign up to set email alerts
|

Viologen Tweezers to Probe the Force of Individual Donor–Acceptor π-Interactions

Abstract: Donor−acceptor (DA) π-interactions are weak attractive forces that are exploited widely in molecular and supramolecular chemistry. They have been characterized extensively by ensemble techniques, providing values for their energies that are useful for the design of soft materials. For implementation of motions or operations based on these DA π-interactions in wholly synthetic molecular machines, the mechanical strength and force associated with their out-ofequilibrium performance are the key parameters, in add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…70 to 80 pN for strong donor-acceptor π-interactions in H 2 O, respectively. 53,54 In our multivalent system, there are 12 possibilities for π-π stacking (5•phenyl, 5•catechol, 2•phenyl from DBCO) leading to forces in the range of several 100 pN. In case of cooperative effects (non-linear increase of force with number of bonds) a further increase of the observed force is possible.…”
Section: Assignment Of Different Interactions Of the Multivalent Systemmentioning
confidence: 96%
“…70 to 80 pN for strong donor-acceptor π-interactions in H 2 O, respectively. 53,54 In our multivalent system, there are 12 possibilities for π-π stacking (5•phenyl, 5•catechol, 2•phenyl from DBCO) leading to forces in the range of several 100 pN. In case of cooperative effects (non-linear increase of force with number of bonds) a further increase of the observed force is possible.…”
Section: Assignment Of Different Interactions Of the Multivalent Systemmentioning
confidence: 96%
“…We previously showed that this approach, based on the physisorption of caught PEG tethers onto the tip, provides a sufficiently strong and stable attachment of the molecule onto the tip to obtain reliable information on the system grafted on the surface. [14][15][16][17][18][19] As a result of the different side chains (Figure 1), the ahelices form under opposite pH conditions, pH > 11 for PLys and pH < 4 for PGA. Immediately prior to performing single-molecule force spectroscopy experiments, the gold substrates were dipped in a diluted solution of the molecules and a passivating agent PEG6-SH was added, to enable single molecules to be individually distributed and immobilized onto the cleaned surface (see Methods section).…”
Section: Resultsmentioning
confidence: 99%
“…Molecular links and knots in proteins have been recognized to impact [220][221][222] significantly on their mechanical strength and stability, as revealed by both theoretical simulations and single-molecule force spectroscopy [223][224][225] . In order to harness these features in smart new materials, mechanical bonds are usually incorporated into synthetic polymers, 226 and their influence on the properties of the polymers evaluated.…”
Section: Applications In Materials Sciencementioning
confidence: 99%